Development of Indonesian Language Learning Media based on Animation Video Using Adobe Premiere Pro Application for Fifth Grade of Elementary Schools - Alwi, Nur Azmi; Ramadani, Fitra; Saralee, Adeweissa (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2024)
This study aims to describe the development of integrated thematic learning media based on video animation using the Adobe Premiere Pro application for fifth grade of elementary schools. This type of research is research and development with the development model being the ADDIE model. The research subjects were teachers and students of fifth grade of public elementary school in VII Koto Sungai Sarik. The participants are 20 people including 10 female students and 10 male students. The results of the study show that the development of integrated thematic learning media based on video animation using the Adobe Premiere Pro application which was developed obtained a validity level of 90.7% for material, 93.7% for language and 88.3% for media with very valid categories. The results of the teacher's response questionnaire obtained a practicality percentage of 95.8%, while the student response questionnaire results obtained a practicality percentage of 95%. This study indicates that the Indonesian Language Learning Media based on Animation Video Using Adobe Premiere Pro Application is sufficient to be used in the learning and teaching in the fifth grade of elementary schools